Tree shaped fractal antenna with multiband characteristics - T P Madhav, B; Subba Reddy, V; Rajasekar Reddy, D; Ravi Sankar, K; V.S.Harsha Ramanujan, E; V.Surya Prakash, V; Venkateshwara Rao, M (International Journal of Engineering and Technology, 2017)
A tree shaped fractal antenna with U shaped slot and W-shaped slot has been designed and analyzed in this article by using ANSYS elec-tromagnetic desktop 17. The proposed antenna is analyzed taking FR4 substrate is taken as the substrate material. The proposed antenna exhibits multiband characteristics (2.75-3.17GHz, 4.1-4.8GHz, 5.1-5.3GHz and 5.4-6.3GHz, 7.21-12.8GHz) in the Ultra-wide band region. The path that is radiating by superposition of the rectangular patches and multiple-band operating frequency is obtained by increasing the U-shapes slots and w-shaped slot on the patch. The improvement in the impedance characteristics between the adjacent frequencies is achieved by using defected ground structure (DGS) on the ground plane as to cover the region of UWB application (3.1-10.6GHz). The proposed antenna works in the applications like Wi-Max, Weather forecasting RADAR systems and WLAN.Â